Enhanced in vitro shoot regeneration and biochemical properties of Stevia rebaudiana using chitosan - Tang, Chu-Nie; Dhilia Udie Lamasudin,; Wan Muhamad Asrul Nizam Wan Abdullah,; Chew, Li Moo; Chiew, Miao-Si; Chai, Qian-Yee; Janna Ong-Abdullah,; Lai, Kok-Song (Penerbit Universiti Kebangsaan Malaysia, 2021)
Stevia rebaudiana is a herbaceous perennial plant with great global demand due to its beneficial steviol glycosides (SGs) content. Current conventional breeding technique is unable to cater the need for more S. rebaudiana planting materials. Therefore, an improved in vitro shoot regeneration protocol was developed for S. rebaudiana by using chitosan. The highest fresh weight of plant (0.586 ± 0.176 g/explant), dry weight of plant (0.056 ± 0.02 g/explant) and plant height (4.94 ± 1.17 cm/explant) with maximum number of leaves (25.33 ± 6.95 /explant) were observed on explants grown in optimun treatment of MS basal medium supplemented with 1.0 mg/L of 6-benzyaminopurine (BAP) and 60 mg/L of low molecular weight (MW) chitosan after 4 weeks of culture. Scanning electron microscopy (SEM) analysis showed that new shoot primordia and shoot bud formation can be seen as early as day 3 and 5 of cultures on optimun treatment. Further biochemical assays showed that total phenolic acid content, total protein content and total hydrolyzed sugar content were recorded higher in explants cultured in optimun treatment as compared to control media. In contrast, total chlorophyll content and total flavonoids content were reduced in optimum treatment. Meanwhile, no significant difference in antioxidant activity was observed. All cultures from the optimal treatment were successfully regenerated, acclimatized and grew well with 100% survival rate. Taken together, an enhanced and efficient shoot regeneration protocol of S. rebaudiana was successfully developed which will be useful for rapid and large-scale micropropagation in future.